I survived the Japanese Tsunami, 2011 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic Press, 2013)
A massive earthquake and devastating tsunami hit Japan while Ben is visiting his late father's hometown, pulling Ben's family apart and leaving him stranded in a strange country during an epic disaster.
650
3-6
Q
4.3
Keywords: Tohoku Earthquake and Tsunami, Japan, 2011 -- Juvenile fiction; Tsunamis -- Japan -- Juvenile fiction; Tohoku Earthquake and Tsunami, Japan, 2011 -- Fiction; Tsunamis -- Japan -- Fiction; Adventure and adventurers -- Fiction; Tsunamis; Tohoku Earthquake and Tsunami, Japan, 2011 -- Fiction; Earthquakes -- Japan -- Fiction; Tsunamis -- Japan -- Fiction; Survival -- Fiction; Japan -- History -- 21st century -- Juvenile fiction; Japan -- History -- Fiction; Japan; Japan -- 2; Adventure fiction; Historical fiction